2005
DOI: 10.1007/s00442-005-0117-1
|View full text |Cite
|
Sign up to set email alerts
|

Influence of habitat, litter type, and soil invertebrates on leaf-litter decomposition in a fragmented Amazonian landscape

Abstract: Amazonian forest fragments and secondgrowth forests often differ substantially from undisturbed forests in their microclimate, plant-species composition, and soil fauna. To determine if these changes could affect litter decomposition, we quantified the mass loss of two contrasting leaf-litter mixtures, in the presence or absence of soil macroinvertebrates, and in three forest habitats. Leaf-litter decomposition rates in second-growth forests (>10 years old) and in fragment edges (<100 m from the edge) did not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
73
1
7

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 110 publications
(94 citation statements)
references
References 34 publications
12
73
1
7
Order By: Relevance
“…Differences in the decomposition rate between the forests fragments studied would be expected to be lower in fragments of early successional phase, since those forests have a more open canopy which influences the microclimate conditions and consequently reduces the decomposers activity (Aerts 1997). Studies on tropical forest succession have showed that environmental conditions for litter decomposition on forests at early successional phase were as favorable as those on forests at late successional phase (Ewel 1976, Xuluc-Tolosa et al 2003, Vasconcelos & Laurance 2005. Besides, Höfer et al (2001) have found similarities in nutrient cycling efficiency by macrofauna communities between disturbed areas (agricultural fields and secondary forests) and mature forests in the central Amazon even though each area had different species.…”
Section: Litter Decomposition Experimentsmentioning
confidence: 99%
“…Differences in the decomposition rate between the forests fragments studied would be expected to be lower in fragments of early successional phase, since those forests have a more open canopy which influences the microclimate conditions and consequently reduces the decomposers activity (Aerts 1997). Studies on tropical forest succession have showed that environmental conditions for litter decomposition on forests at early successional phase were as favorable as those on forests at late successional phase (Ewel 1976, Xuluc-Tolosa et al 2003, Vasconcelos & Laurance 2005. Besides, Höfer et al (2001) have found similarities in nutrient cycling efficiency by macrofauna communities between disturbed areas (agricultural fields and secondary forests) and mature forests in the central Amazon even though each area had different species.…”
Section: Litter Decomposition Experimentsmentioning
confidence: 99%
“…Entretanto, nas florestas fragmentadas as árvores típicas da floresta primária são substituídas por espécies pioneiras de crescimento rápido e de baixa longevidade (Laurance et al 2006, Michalski et al 2007, o que pode acarretar um aumento no turnover do carbono. o aumento na quantidade de plantas pioneiras próximo às bordas afeta a dinâmica da produção e decomposição da serapilheira (Didham 1998, Vasconcelos & Laurance 2005, Vasconcelos & Luizão 2004). a taxa de produção de serapilheira é bem maior nas bordas dos fragmentos de floresta (Figura 8), em parte devido à menor longevidade e ao crescimento acelerado das folhas das plantas pioneiras que dominam as bordas dos fragmentos de floresta Figura 8.…”
Section: Mudanças Nos Processos Ecossistêmicosunclassified
“…Microclimatic changes near edges, such as reduced humidity, increased light, and greater temperature variability, penetrate up to 60 m into fragment interiors (Kapos 1989) and can negatively affect species adapted for humid, dark forest interiors (Lovejoy et al 1986, Benitez-Malvido 1998. Leaf litter accumulates near edges (Carvalho and Vasconcelos 1999 Edge penetration distance (m) Didham and Lawton 1999) because drought-stressed trees shed leaves and possibly because drier edge conditions slow litter decomposition (Kapos et al 1993, Didham 1998, Vasconcelos and Laurance 2005. Accumulating litter may negatively affect seed germination (Bruna 1999) and seedling survival (Scariot 2001) and makes forest edges vulnerable to surface fires during droughts (Cochrane et al 1999).…”
Section: Edge Effectsmentioning
confidence: 99%